TATA KELOLA SAINS DI LEMBAGA PENDIDIKAN ISLAM MELALUI PENATAAN LABORATORIUM: SCIENCE GOVERNANCE IN ISLAMIC EDUCATIONAL INSTITUTIONS THROUGH LABORATORY ARRANGEMENT - Hidayatulloh, M. Deni; Irawan; Priatna, Tedi (CV. Kalimasada Group, 2023)
The research aims to reveal data on science governance in Islamic educational institutions through the arrangement of laboratories at MAN 1 Bekasi school, on how the planning, implementation, and evaluation of laboratory management at the school. This research method uses a qualitative method by conducting interviews and observations at the school concerned to obtain information and data collection in science governance at the MAN 1 Bekasi school.